Perancangan Sistem dan Aplikasi Manajemen Kinerja (Studi Kasus : UPT TRANS PADANG) - Difana Meilani; Yumi Meuthia; Idham Afandi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Performance is the result or the overall success rate of a person during a certain period in performing the task. As a form of government efforts to solve the problems of transport in the city of Padang, Padang Trans supposed to have a standard of service quality and performance management systems. The design of the performance management system in Trans UPT Padang use the help of four perspectives of the balanced scorecard. By way of formulating the strategic objectives and Key Performance Indicator (KPI) and then look for connection between them and perform weighting to determine the ranking and the weight of each KPI. KPI weighting using Analytical Hierarchy Process (AHP). Results of weighting and weighting the ranking shows KPI's performance Trans UPT Padang. These results are then used as the source of the design of performance management applications. Performance management system application design and development of system models using waterfall method. From system design uses four perspectives of the balanced scorecard produces 9 strategic objectives derived from the vision, mission and objectives of the company. Then obtained 13 (thirteen) KPI from questionnaires and interviews were subsequently obtained the weight of each KPI weighting of the results of the questionnaire pairwise comparisons.